Answer:
see explanation
Step-by-step explanation:
A
Given
= (n² + n) ← multiply each term in the parenthesis by
= n² + n
B
To find the sum of the first 12 whole numbers, substitute n = 12 into the formula, that is
= (12² + 12) = (144 + 12) = × 156 = 78
A)
B) 78
B) To find the sum of first 'n' whole numbers , formula used is :-
We have to find the sum of first 12 whole numbers . So here n = 12
Putting the value of 'n' in above formula ,
166 2/3 hope this helps
VERTICAL
question 4
using sine rule:
question 5
using cosine rule:
5x-4y+4
3x-4y-2+2x+6
Gathers like terms together:
3x+2x= 5x
-4y= -4y
-2+6= 4
Put it together:
Down